KAJIAN HUKUM PIDANA TERHADAP PEDAGANG KAKI LIMA (PKL) YANG MENGGUNAKAN FASILITAS UMUM UNTUK BERJUALAN DI TAMAN BUNDARAN TIROSA KOTA KUPANG - Liu, Daud Jonatan; Manafe, Deddy R. CH.; Djara Dima, Adrianus (Petitum Law Journal, 2024)
The Kupang City Environment and Hygiene Service (LHK) and UPTD Park installed a sign prohibiting selling in the Tirosa statue roundabout area. Facts show that street vendors are still selling at the end of park and on the shoulders of roads. This research is empirical legal research that examines all legal events that have occurred through a case approach. Data collection was carried out by interview and document study. Tthe data is presented in a qualitative descriptive manner. The results of this research show that criminal law regulations for traders who use public facilities to sell have been regulated in Kupang City Regional Regulation 56 of 2002 concerning Regulation of Business Places and Development of Street Vendors in Kupang City. The application of criminal law for traders who use public facilities to sell at Tirosa Roundabout Park, Kupang City can involve several relevant legal aspects, depending on the type of violation committed. Punishments can take the form of administrative sanctions, fines, or even business closure. Therefore, a comprehensive and sustainable approach is needed to managing street vendors by Involving stakeholders, education, and designing supportive policies can create a more orderly and mutually beneficial environment for all parties.